1989
DOI: 10.1111/j.1476-5381.1989.tb12589.x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent affinity of 1,3‐dipropyl‐8‐cyclopentylxanthine for adenosine A1 and A2 receptors in isolated tissues from guinea‐pigs

Abstract: 1 The classification of adenosine receptor subtypes (A1 and A2) in intact tissues has been based on the order of agonist potency. In this study the apparent affinity of 1,3-dipropyl-8-cyclopentylxanthine (CPX), an antagonist which has been reported to be Al selective, and the nonselective antagonist 1,3-dimethyl-8-phenylxanthine (8PT) has been evaluated on isolated tissues from the guinea-pig.2 The isolated tissues used were atria (bradycardic response, proposed Al sub-type), aorta and trachea (relaxant respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 18 publications
4
27
1
Order By: Relevance
“…CPX has been shown to exhibit selective Al-receptor affimity in rat brain membranes (Bruns et al, 1987) and, more recently, has been shown to be Al-selective in guinea-pig isolated tissues (Collis et al, 1989). In our experiments CPX produced an approximately 10 fold shift in the anti-adrenergic response of adenosine in guinea-pig myocytes at a concentration of 3.5 nM.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…CPX has been shown to exhibit selective Al-receptor affimity in rat brain membranes (Bruns et al, 1987) and, more recently, has been shown to be Al-selective in guinea-pig isolated tissues (Collis et al, 1989). In our experiments CPX produced an approximately 10 fold shift in the anti-adrenergic response of adenosine in guinea-pig myocytes at a concentration of 3.5 nM.…”
Section: Discussionmentioning
confidence: 52%
“…Calcium concentration-response curves were also cumulative and were performed in a phosphate-free Krebs-Henseleit solution to prevent precipitation at high concentrations of calcium (up to 25mm). 8-Cyclopentyl 1,3-dipropylxanthine (CPX) was used as a selective Al-receptor antagonist (Collis et al 1989). Cells were exposed to CPX 15 min before the adenosine concentration-response curve was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…The inotropic responses of PDE inhibition and P-adrenoceptor stimulation were further compared to that of maximum concentrations of CPT cyclic AMP, an analogue of cyclic AMP (Collis et al, 1989). Again there was no significant difference, from that of IBMX, in the extent of potentiation over maximum isoprenaline in either group of guinea-pig ventricular myocytes ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…The xanthine, PD1 15199 (1,3 dipropyl-8-N-[2-dimethylamino) ethyl]-N-methyl-4-2, 3,6, 7-tetrahydro-2,6-dioxo) -benzenesulphonamidexanthine), although having higher affinity for the A2a binding site than the A2b binding site, is equipotent at A2a and A1 binding sites (Bruns et al, 1987b). PD1 16948 (8-cyclopentyl-1-3-dipropylxanthine) has higher affinity for the A1 receptor than for A2a binding sites in rat brain studies (Bruns et al, 1987a,b;Jarvis et al, 1989) and clearly demonstrated A1-selective antagonism in guinea-pig isolated tissues (Collis et al, 1989). To date, the most A2a-selective xanthine antagonist is 8-(3-chlorostyryl)-1,3-dipropylxanthine which in binding studies demonstrates A2a A1 selectivity of 520 fold but only 22 fold in functional tests (Jacobson et al, 1993).…”
Section: Introductionmentioning
confidence: 99%